Pengaruh Atribut Islami, Kelengkapan Produk, dan Harga terhadap Loyalitas Konsumen pada Toko Basmalah Cabang Plumbon, Pandaan, Pasuruan - Nirza Balqisa Mabruroh; Nur Dinah Fauziah (Prodi Ekomoni Syariah STAI Al Akbar Surabaya, 2024)
In Indonesia, retail sales growth in 2023 has increased to around 4% or in line with Indonesia's economic growth of around 5.5%, according to the Indonesian Retailers Association (APRINDO). The increase in retail is also accompanied by consumptive behavior, the population continues to grow, and the need for consumers to meet their needs. This study is entitled